European corporate law. 2nd ed. - Dorresteijn, Adriaan; Monteiro, Tiago; Teichmann, Christoph; Werlauff, Erik (The Hague, 2009)
"In the past few years, the European Commission and the European Court of Justice have each in their own way contributed to a resurgence of the harmonisation programme in corporate law. The Court’s trilogy of its Centros, Überseering and Inspire Art judgements have marked a fundamental policy switch regarding the right of establishment for companies and other legal entities. And, perhaps most significantly, the Commission is now encouraged to launch a draft Statute for a European Private Company which it is hoped will be a supranational business organisation as was originally envisaged for the SE. However, notwithstanding these developments, at the national level diversity is still the key word for those who try to understand corporate laws within the EU.